Implementing the IBM System Storage SAN Volume Controller V6.1 - Tate, Jon; Bernasconi, Angelo; Chabrol, Alexandre; Crowhurst, Peter; Enders, Frank; MacQuarrie, Ian (IBM Redbooks, 2011)
This IBM® Redbooks® publication is a detailed technical guide to the IBM System Storage® SAN Volume Controller (SVC) Version 6.1.0. SAN Volume Controller is a virtualization appliance solution which maps virtualized volumes that are visible to hosts and applications to physical volumes on storage devices. Each server within the storage area network (SAN) has its own set of virtual storage addresses that are mapped to physical addresses. If the physical addresses change, the server continues running using the same virtual addresses that it had before. Therefore, volumes or storage can be added or moved while the server is still running. The IBM virtualization technology improves the management of information at the "block" level in a network, thus enabling applications and servers to share storage devices on a network. This book is intended for readers who need to implement the SVC at a 6.1.0 release level with a minimum of effort.